Echogenic liquor at term pregnancy on ultrasonography is not always meconium - Shrestha, Shreejana; Bhandary, Shital; Dwa, Yogita; Jaiswal, Pooja; Parmar, Binod; Karki, Dan B (Journal of Patan Academy of Health Sciences, 2017)
Introductions: The presence of echogenic amniotic fluid at term pregnancy on sonography is uncommon. Finding of meconium in the amniotic fluid by ultrasound is used to predict mode of delivery of fetus, fetal wellbeing and risk of intrauterine fetal demise. We aim to observe the clinical significance of echogenic liquor at term pregnancy. Methods: This was a retrospective study of 102 cases of echogenic liquor at gestation age between 36 and 41 weeks (term pregnancy) during five years 2010 to 2015A.D. Amniotic fluid index (AFI) was calculated. Fluid was observed for presence of vernix caseosa or meconium stain during spontaneous and artificial rupture of membrane. The APGAR score of baby was taken twice at 5 and 10 minutes. Results: Among the 102 patients with echogenic amniotic fluid at term, 83 (81.4%) were vernix and 19 (18.6%) had meconium stain. Low APGAR scores were found in 5 (0.9%) and normal score in 97 (95.1%) indicating good fetal outcome. Among these cases, 89 (87.3%) had normal AFI and 13 (12.7%) had decreased liquor. Conclusions: There were no association between echogenic liquor and meconium stain, AFI or APGAR score of the baby in term pregnancy.